A giant aggressive angiomyxoma of the vulva in a dwarf: a rare case report - Mukherjee, Shubhra; Advait Prakash; Hemlata Sodhiya; Sarika Jaiswal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Aggressive angiomyxoma is a rare soft tissue tumour that carries a high risk of local relapse. The tumour usually arises from the pelvic and perineal regions. We presented a case of a young girl with dwarfism, mental retardation and thyroid agenesis who presented with aggressive angiomyxoma of the vulva. As it is almost exclusively seen in women of reproductive age group, this is the first case reported in a teenage girl, to the best of our knowledge. A mentally retarded girl, aged fifteen years, presented with a large mass hanging from the vulva, with ulceration over the mass. She had short stature, anasarca, mental retardation, primary amenorrhoea, under-developed secondary sexual characters .and thyroid agenesis. Local examination revealed a pedunculated mass of 15 by 4 cm size arising from the mons pubis closely resembling a giant penis. Full hormonal and radiological work-up was done. Her condition was optimized and the mass was removed with wide excision of margins followed by cystoscopy under general anaesthesia. Histopathology and immunohistochemistry were suggestive of aggressive angiomyxoma. She has no recurrence till date. Despite its rarity, angiomyxoma should be considered in the differential diagnosis of any painless swelling located in the genitofemoral region. The principal treatment is surgical excision. Long term follow-up is needed due to its high tendency of local recurrence.